Gambaran Kecemasan dan Mekanisme Koping Mahasiswa Program Studi Sarjana Keperawatan Tingkat 1 Dalam Menghadapi Ujian Praktik Laboratorium - Pasongli, Gabriella Cintya; Ricky, Denny Paul (NUTRIX, 2024)
Anxiety is a person's emotional status that arises against situations in the environment, both from within the individual and outside the individual. Anxiety can lead to loss of concentration, especially in students who will take the laboratory practicum exam. Anxiety experienced by individuals will determine the coping mechanism that will be used in overcoming the problem. The purpose of this study was to obtain a description of the anxiety and coping mechanisms of first-year nursing undergraduate students in facing laboratory practical exams. The research method used was descriptive quantitative using total sampling technique with 80 respondents. Data collection using the State Anxiety Inventory questionnaire and The Brief Cope Inventory. This study shows that the anxiety of first-year nursing undergraduate students in facing laboratory practical exams is in the mild anxiety category. Coping of first-year nursing undergraduate students in facing laboratory practice exams is adaptive coping and uses problem-focused coping. Kecemasan merupakan status emosional seseorang yang muncul terhadap situasi di lingkungan, baik dari dalam individu maupun luar individu. Kecemasan dapat mengakibatkan hilangnya konsentrasi terutama pada mahasiswa yang akan mengikuti ujian praktikum laboratorium. Kecemasan yang dialami oleh individu akan menentukan mekanisme koping yang akan digunakan dalam mengatasi masalah tersebut. Tujuan penelitian ini adalah untuk mendapatkan gambaran kecemasan dan mekanisme koping mahasiswa Program Studi Sarjana Keperawatan Tingkat 1 dalam menghadapi ujian praktikum laboratorium. Metode penelitian yang digunakan adalah deskriptif kuantitatif menggunakan teknik total sampling dengan jumlah responden 80 orang. Pengumpulan data menggunakan kuesioner State Anxiety Inventory dan The Brief Cope Inventory. Penelitian ini menunjukkan bahwa kecemasan mahasiswa Program Studi Sarjana Keperawatan Tingkat 1 dalam menghadapi ujian praktik laboratorium adalah pada kategori kecemasan ringan. Koping mahasiswa Program Studi Sarjana Keperawatan Tingkat 1 dalam menghadapi ujian praktik laboratorium adalah koping adaptif dan menggunakan problem-focused coping.